Computer-interfacing design for real time signal classification using fuzzy: article/ Mohd Hairey Abdul Halim - Abdul Halim, Mohd Hairey (2005)
It is aim to classify and display the real time signal in frequency through computer. The process involved the used of AI (Artificial Intelligence) technique. Software based on MATLAB Fuzzy Toolbox and MATLAB Simulink will be used to develop the fuzzy logic. The real time input signal based on the specify frequency generated by the signal generator will be insert to the fuzzy logic controller through the computerinterfacing system that will be built and designed based on RS-232 communication. The output will be displayed through the computer based on the classification of the frequency signal set in the membership function.